THE CONCEPT OF TAUHID EDUCATION VALUE (AQIDAH) IN NATIONAL EDUCATION SYSTEM PERSPECTIVE - Nurhadi, Nurhadi; Lubis, Zainul Bahri (STAI Hubbulwathan Duri, 2019)
This study aims to determine the values of Tauhid Education in the National Education System and the relevance of the National Education System Law No. 20 of 2003 in strengthening the values of Tauhid Education. This research method uses a type of library research or literature study (library research). Using two data sources, namely: 1). The primary data is law No. 20 of 2003 concerning the National Education System. 2). Secondary data is literature related to this research. The results of the study were obtained: 1) the values of Tauhid education contained in Chapter II Article 3 read: